Experiences of the Geography Subject Advisors in the Implementation of Geographic Information Systems in KwaZulu-Natal Province - Thulasizwe Fredrick Mkhize (Research in Social Sciences and Technology- OpenED Network, 2023)
This paper explored the experiences of geography subject advisors (GSAs) in the implementation of Geographic Information Systems (GIS) in South African schools. This was done to determine how they assist in the implementation of GIS. National senior certificate diagnostic reports for matric results indicate every year that learners are performing poorly in the GIS section of geography subject. The current literature shows that there is a lack of pedagogical content knowledge in geography teachers in the teaching and learning of GIS. Several scholars have written about learners and educators in the implementation of GIS in schools, but there is a lack of literature on GSAs’ experiences in the implementation of GIS in schools. This paper is underpinned by instructional leadership theory, which argues for leadership to focus their efforts on implementing of practices that positively impact students’ learning. Qualitative research approach, and semi-structured interviews were used to generate data to answer the research questions. Two GSAs from two selected districts were purposively chosen to participate in this study. The findings showed that GSAs organise workshops for educators. However, certain educators do not attend workshops and other workshops which are planned, do not materialise. GSAs rely on geography educators that are knowledgeable about GIS to assist in workshops by teaching others. GIS teaching in schools was aledged to be focused on a theoretical aspect without integrating the practical part. The study proposes that the DBE in collaboration with higher education institutions, should provide GIS teacher training opportunities for teachers.